Novel Microchip-Based Tools Facilitating Live Cell Imaging and Assessment of Functional Heterogeneity within NK Cell Populations - Forslund, Elin; Guldevall, Karolin; Olofsson, Per E.; Frisk, Thomas; Christakou, Athanasia; Wiklund, Martin; Önfelt, Björn (Frontiers in Immunology, 2012)
Each individual has a heterogeneous pool of NK cells consisting of cells that may be specialized towards specific functional responses such as secretion of cytokines or killing of tumor cells. Many conventional methods are not fit to characterize heterogeneous populations as they measure the average response of all cells. Thus, there is a need for experimental platforms that provide single cell resolution. In addition, there are also transient and stochastic variations in functional responses at the single cell level, calling for methods that allow studies of many events over extended times. This paper presents a versatile microchip platform enabling long-term microscopic studies of individual NK cells interacting with target cells. Each microchip contains an array of microwells, optimized for medium or high-resolution time-lapse imaging of single or multiple NK and target cells, or for screening of thousands of isolated NK-target cell interactions. Individual NK cells confined with target cells in small microwells is a suitable setup for high-content screening and rapid assessment of heterogeneity within populations, while microwells of larger dimensions are appropriate for studies of NK cell migration and sequential interactions with multiple target cells. By combining the chip technology with ultrasonic manipulation, NK and target cells can be forced to interact and positioned with high spatial accuracy within individual microwells. This setup effectively and synchronously creates NK-target conjugates at hundreds of parallel positions in the microchip. Thus, this facilitates assessment of temporal aspects of NK-target cell interactions, e.g. conjugation, immune synapse formation and cytotoxic events. The microchip platform presented here can be used to effectively address questions related to fundamental functions of NK cells that can lead to better understanding of how the behavior of individual cells add up to give a functional response at the population level.